Reduced Activity of Hypothalamic Corticotropin-Releasing Hormone Neurons in Transgenic Mice with Impaired Glucocorticoid Receptor Function - Dijkstra, Ivar (J Neurosci, 1998)
Loss of central glucocorticoid receptor (GR) function is thought to be involved in the development of neuroendocrine and psychiatric disorders associated with corticotropin-releasing hormone (CRH) hyperactivity. The possible causal relationship between defective GR function and altered activity of CRH neurons was studied in transgenic mice (TG) expressing antisense RNA against GR. Immunocytochemical studies showed significant reductions in CRH immunoreactive neurons in the paraventricular nucleus (PVN) and in CRH and vasopressin (AVP) stores in the external zone of the median eminence. Concomitantly, stimulus-evoked CRH secretion from mediobasal hypothalami of TG micein vitro was reduced significantly. However, CRH mRNA levels in the PVN of TG mice were marginally lower than those in wild-type (WT) mice. (125)I-CRH binding autoradiography revealed no differences between WT and TG animals in any of the brain regions that were studied. Basal plasma corticosterone (cort) levels and (125)I-CRH binding, CRH-R(1) mRNA, POMC mRNA, and POMC hnRNA levels in the anterior pituitary gland were similar in WT and TG mice. Intraperitoneal injection of interleukin-1β (IL-1β) increased plasma cort levels, CRH mRNA in the PVN, and anterior pituitary POMC hnRNA similarly in WT and TG mice. The injection of saline significantly reduced anterior pituitary CRH-R(1) mRNA levels in WT mice, but not in TG mice, whereas IL-1β produced a decrease in these mRNA levels in both strains. The data show that long-term GR dysfunction can be associated with reduced activity of CRH neurons in the PVN and decreased sensitivity of pituitary CRH-R(1) mRNA to stimulus-induced downregulation. Moreover, the hypothalamic changes observed in this model suggest that impaired GR function, at least if present since early embryonic life, does not necessarily result in CRH hyperexpression characteristics of disorders such as major depression.